Local political chief turnover and economic growth: Evidence from China. Issue 3 (11th May 2020) - Wu, Jing; Li, Hao; Li, Keyang
Abstract: It is widely believed that the rotation and promotion system of local political chiefs plays an important role in China's economic miracle. In this paper, however, we focus on the potential cost of the inherent frequent turnover of local chiefs. Based on a new manually collected dataset on prefectural‐level local chiefs between 1983 and 2012, our empirical results suggest that the turnover of the local Chinese Communist Party (CCP) chief would lead to a 0.48 percentage point decrease in the local GDP growth rate in the current year. This effect is especially concentrated on more government‐affected fields, such as domestic investments, consumption and government expenditures. We also provide evidence that organization friction, especially the successor CCP chiefs' unfamiliarity with the city, his/her new colleagues and/or the working conditions, is one of the major potential reasons for such a negative turnover effect.